2015
DOI: 10.1627/jpi.58.71
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Solid Oxide Fuel Cells Using LaGaO<sub>3</sub>-based Oxide Electrolyte on Metal Support

Abstract: Solid oxide fuel cells (SOFCs) can directly convert the chemical energy of various fuels to electric power with unmatched energy conversion efficiency. The oxide ion conductivity of LaGaO3 doped with Sr and Mg (LSGM) is introduced and application of LSGM to low temperature SOFCs is explained. Power density at lower temperature was dramatically increased by application of LSGM film manufactured with laser ablation techniques. By application of a suitable buffer layer, the cell using LSGM thin film electrolyte h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] According to various reported studies, La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3 (LSGM) has been considered as a promising electrolyte material for IT-SOFCs in the temperature range of 600-800 C owing to its higher ionic conductivity and stability over a broad range of O 2 partial pressures. The ionic conductivity of LSGM has been reported to be almost >0.005 S cm À1 at 500 C which is comparable to that of conventional yttria-stabilized zirconia (YSZ) which shows this ionic conductivity at 680 C. 9,10 In addition, LSGM possesses remarkable chemical compatibility with various perovskite electrode materials employed in SOFCs. Pure LaGaO 3 offers poor conductivity.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…[1][2][3][4][5][6][7][8] According to various reported studies, La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3 (LSGM) has been considered as a promising electrolyte material for IT-SOFCs in the temperature range of 600-800 C owing to its higher ionic conductivity and stability over a broad range of O 2 partial pressures. The ionic conductivity of LSGM has been reported to be almost >0.005 S cm À1 at 500 C which is comparable to that of conventional yttria-stabilized zirconia (YSZ) which shows this ionic conductivity at 680 C. 9,10 In addition, LSGM possesses remarkable chemical compatibility with various perovskite electrode materials employed in SOFCs. Pure LaGaO 3 offers poor conductivity.…”
Section: Introductionmentioning
confidence: 86%
“…In the case of LSGM, impurity phases were increased with an increased ratio of La site/Ga site ions which is responsible for the reduction of the corresponding conductivity. 12 Ishihara et al 9 continued their studies to investigate the effect of a small amount of rare earth (neodymium (Nd), samarium (Sm), gadolinium (Gd), yttrium (Y), etc.) cations on the conductivity of the doped La site in LSGM and concluded that total conductivity was minimized and the magnitude relationship of conductivity was as follows: Nd 3+ > Sm 3+ > Gd 3+ > Y 3+ > Yb 3+ .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…z E-mail: nhperry@illinois.edu perovskite electrodes. [7][8][9] Compared to well-established fluoritestructured yttria stabilized zirconia electrolytes, which have ionic transference numbers close to 1 across a wide range of oxygen partial pressures, 10 LSGM can exhibit non-negligible p-type electronic conductivity under oxidizing conditions. [11][12][13] In LaGaO 3 , the process of ionic compensation with oxygen vacancies (v •• O ) for Sr-and Mg-acceptor doping can be presented in Krӧger-Vink notation by:…”
mentioning
confidence: 99%